2012
DOI: 10.1111/j.1540-6237.2012.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Latino School Concentration and Academic Performance among Latino Children

Abstract: Objective To examine the effects of the concentration of Latino students in elementary schools on Latino first graders’ test scores, and to determine if the effects vary by children's nativity status. Methods We use generalized estimating equations (GEE) on a sample of Latino first graders from the Early Childhood Longitudinal Study‐Kindergarten Class of 1998 (ECLS‐K). Results For math and reading, Latino concentration in schools improves students’ first grade test scores for Latino children of immigrants, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…When supported financially and organizationally, these environments can produce desirable outcomes. Recent research indicates such contexts limit feelings of social isolation, increase solidarity, enhance academic self-concept and aspirations, improve test performance, and foster a greater capacity to link one’s racialized group status to educational success (Cuellar 2014; Goldsmith 2004; Lee and Klugman 2013; Salerno and Reynolds 2017). However, portraits of MSIs can sometimes be painted with an overly broad brush, overlooking their distinct histories (Espino and Cheslock 2008), missions (Contreras et al 2008), and, as we argue, efforts to redress racialized inequality in higher education.…”
Section: Msis In Higher Educationmentioning
confidence: 99%
“…When supported financially and organizationally, these environments can produce desirable outcomes. Recent research indicates such contexts limit feelings of social isolation, increase solidarity, enhance academic self-concept and aspirations, improve test performance, and foster a greater capacity to link one’s racialized group status to educational success (Cuellar 2014; Goldsmith 2004; Lee and Klugman 2013; Salerno and Reynolds 2017). However, portraits of MSIs can sometimes be painted with an overly broad brush, overlooking their distinct histories (Espino and Cheslock 2008), missions (Contreras et al 2008), and, as we argue, efforts to redress racialized inequality in higher education.…”
Section: Msis In Higher Educationmentioning
confidence: 99%
“…It has been indicated that concentration is the capacity to maintain attention with precision [9]. In addition, it has been reported that good concentration improves schoolchildren's performances on academic tests [10]. In this context, one study showed that attention and concentration are fundamental in cognitive performance [11].…”
Section: Introductionmentioning
confidence: 99%
“…Schools with high proportions of minority and/or Free and Reduced Price Lunch eligible students are clear targets for educational intervention. Schools with higher proportions of minorities and/or Latinos/as often have more targeted resources for learning, such as Title 1 funding, minority teachers, ELL teachers, and professional development geared towards meeting the needs to specific populations (Goldsmith 2003; Lee and Klugman 2013; Potochnick and Handa 2012). Mexican-origin students may also have greater co-ethnic parental support in high-Latino/a schools (Klugman, Lee, and Nelson 2012).…”
Section: Introductionmentioning
confidence: 99%